Mingantu Spectral Radioheliograph for Solar and Space Weather Studies - Yan, Yihua; Chen, Zhijun; Wang, Wei; Liu, Fei; Geng, Lihong; Chen, Linjie; Tan, Chengming; Chen, Xingyao; Su, Cang; Tan, Baolin (Frontiers in Astronomy and Space Sciences, 2021)
The Chinese Spectral Radioheliograph (CSRH) covering 400 MHz-15 GHz frequency range was constructed during 2009–2016 in Mingantu Observing Station, National Astronomical Observatories, Chinese Academy of Sciences at Zhengxiangbaiqi, Inner Mongolia of China. The CSRH is renamed as MingantU SpEctral Radioheliograph (MUSER) after its accomplishment. Currently, MUSER consists of two arrays spreading over three spiral-shaped arms. The maximum baseline length is ∼3 km in both east-west and north-south directions. The MUSER array configuration is optimized to meet the needs of observing the full-disk Sun over ultrawide wavebands with images of high temporal, spatial and spectral resolutions and high dynamic range. The low frequency array, called MUSER-I, covers 400 MHz-2.0 GHz with 40 antennas of 4.5-m-diameter each and the high frequency array, called MUSER-II, covers 2–15 GHz with 60 antennas of 2-m-diameter each. The MUSER-I can obtain full-disk solar radio images in 64 frequency channels with a time cadence of 25 ms and a spatial resolution of 51.6″ to 10.3″ (corresponding to the frequency range 400 MHz to 2 GHz), whereas the MUSER-II can obtain full-disk solar images in 520 channels with a time cadence of 206.25 ms and a spatial resolution of 10.3″ to 1.3 (corresponding to the frequency range 2 to 15 GHz). A dynamic range of 25 dB can be obtained with snapshot images produced with the MUSER. An extension of MUSER in the further lower frequency range covering 30–400 MHz with an array of 224 logarithm-periodic dipole antennas (LPDAs) has been approved and will be completed during the next 4 years. The MUSER, as a dedicated solar instrument, has the following advantages providing simultaneous images over a wide frequency range with a unique high temporal-spatial-spectral resolutions; high-performing ultrawide-band dual-polarization feeds for wide-band signal collection; advanced high data-rate, large-scale digital correlation receiver for multiple-frequency and faster snapshot observations; and applications of new technologies such as using optical fiber to obtain remote antenna and wide-band analog signal transmission. The MUSER thus provides a unique opportunity to measure solar magnetic fields and trace dynamic evolution of energetic electrons in several radio frequencies, which, in turn, will help to have better understandings of the origin of various solar activities and the basic drivers of space weather.